Colorimetry by Assessment TwAc Booster System Efficiency - Yudin, Michael A. (International Journal of Psychosocial Rehabilitation, 2020)
Background: Ever-increasing demand for cosmetic correction of evolutional changes of facial skin dictates the search of methods having pathogenetic mechanism influencing aging processes and provide a long-term therapeutic effect. Methods: The author offered a complex correction of facial skin aging symptoms using optimum doses of botulinum toxin A and least traumatic booster system on the basis of TwAc polynucleotides. A high clinical performance of the method is provided through the synergy of the biological effect of the selected preparations and pathogenetics of their influence on skin structural elements. High efficiency and low injury rate of the describe method allows applying it in mass dermatocosmetological practices. Results: Achieved results are accessed by means of colorimetry which vividly and accessibly for the patients reflects dynamics of positive changes in skin problem areas. Colorimetric characteristics of the involutional changed facial skin: shade shift of the facial basic color to the violet zone of the spectrum (HUE 10º–40º), slight color intensity (Chroma 4.2-5.1), reflection low level is stipulated by the decreased tension, increased folding, depleted skin vascular component, increased content of melanin agent and oxyhemoglobin decreased level. Conclusions: Application of complex correction method for involutional changed facial skin in long dates after procedure.